The impact of Yangtze River discharge on the genetic structure of a population of the rock bream, Oplegnathus fasciatus. Issue 4 (20th April 2016) - Xiao, Yongshuang; Ma, Daoyuan; Dai, Ming; Liu, Qinghua; Xiao, Zhizhong; Li, Jun; Liu, Jing; Xu, Shihong; Cheng, Qiqun
ABSTRACT: As a rocky reef species, Oplegnathus fasciatus displays significant geographic differences that may be congruent with patterns of molecular variation. We used 10 polymorphism microsatellite loci to characterize the genetic structure and test the impact of ocean currents and the Yangtze River on the population genetic connectivity of the rock bream, O. fasciatus, sampled from Jiaonan (JN), Zhoushan (ZS) and Taiwan (TW). The average number of alleles was 17.78, with a total of 160 alleles, and the average allele value in the East China Sea (ZS = 13.70) was higher than that in the Yellow Sea (JN = 6.70). The individuals at the ZS location showed the highest expected heterozygosity (He   = 0.86), Nei's genetic diversity ( H  = 0.84) and Shannon genetic diversity ( I  = 2.21). Genetic bottleneck tests showed that individuals had experienced a recent bottleneck effect in the JN location. AMOVA analysis showed that 12.19% of genetic variation existed among populations, indicating significant population genetic differentiation in the species. The values of the population pairwise differentiation index ( F st and Φ pt ) ranged from 0.01 to 0.29. The UPGMA tree showed two diverged genealogical branches corresponding to sampling localities (Clade A = JN, Clade B = ZS and TW) in the species. The AMOVA and STRUCTURE analyses suggested that O. fasciatus may be composed of two stocks in the examined range, and the freshwater discharge from the Yangtze River might act as a physical barrier to genetic exchange between north and south China stocks of the species.